Empirical Analysis of The Impact of Director Characteristics on Carbon Emission Disclosure: Internal Audit as a Moderating - Arum Ardianingsih; Hikma Markhatus Sholekha; Komala Ardiyani (Institut Bisnis dan Informatika Kesatuan, 2026)
Disclosure of information on carbon emissions is carried out by companies to meet the demands of their stakeholders. This study aims to obtain empirical evidence that board size, board independence, and gender influence emission disclosure, which is strengthened by the existence of internal controls. The study used energy companies in Indonesia as the research object. A total of 84 research data were used. Moderation regression analysis was conducted in this study using the Chow Test, Hausman Test, Lagrange Multiplier Test, and the common effect model. The results of the study show that board size, board independence, and gender have a positive effect on carbon emission disclosure. In addition, internal audit also strengthens the influence of board size, board independence, and gender on carbon emission disclosure. The practical implication of this study for companies is that a governance system is needed to ensure the company's financial and non-financial performance can be achieved. Disclosure of carbon emissions can show non-financial environmental performance that is useful for its stakeholders.